2020
DOI: 10.1080/14616696.2020.1818271
|View full text |Cite
|
Sign up to set email alerts
|

The ‘lonely raver’: music livestreams during COVID-19 as a hotline to collective consciousness?

Abstract: This paper offers an explorative analysis of the online social practices of livestreamed concerts as one of the most popular cultural outlets during the COVID-19 imposed 'lockdown' in Europe. Ritual theory is used to investigate the potential of these virtual concerts in generating a collective consciousness, and the related feelings of social solidarity and resilience, specifically important in times of physical isolation. Through a thematic content analysis of the comments (n = 1501) posted during livestream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 23 publications
2
52
0
2
Order By: Relevance
“…Likewise, Morris' recent research (2020) shows that music workshops are presented as an affective conditioning factor in the perception of temporal and spatial reality of immigrants held in British detention centers. This evidence, together with others on the contributions of music livestreams in the creation of collective consciousness and social solidarity during the COVID-19 (Vandenberg et al, 2020), explains how the practice of music, regardless of its format, can be able to attenuate loneliness and isolation and, in some way, favorably affect an increase in resilience.…”
Section: Discussionmentioning
confidence: 64%
“…Likewise, Morris' recent research (2020) shows that music workshops are presented as an affective conditioning factor in the perception of temporal and spatial reality of immigrants held in British detention centers. This evidence, together with others on the contributions of music livestreams in the creation of collective consciousness and social solidarity during the COVID-19 (Vandenberg et al, 2020), explains how the practice of music, regardless of its format, can be able to attenuate loneliness and isolation and, in some way, favorably affect an increase in resilience.…”
Section: Discussionmentioning
confidence: 64%
“…Unsurprisingly, online communication technologies are a major conduit for people to counter their isolation during lockdowns. In this context, music has also served as a means to bring solidarity amongst isolated people through online livestreams (Vandenberg et al 2020). Other research employing Twitter data (Iranmanesh and Alpar Atun 2020) measures the changes in tweets' mean geographical distance between the pre-pandemic and pandemic periods.…”
Section: Solidarity and Cohesionmentioning
confidence: 99%
“…It has been shown that social interactions through music can effectively reduce feelings of loneliness and provide a sense of togetherness and belonging (Labbé et al, 2007;Laukka, 2007;Miranda and Claes, 2009;Tymoszuk et al, 2020). This may explain a general trend observed across the globe regarding the use of music through online musical gatherings (e.g., live music streams and concerts) as a positive coping strategy to deal with feelings of loneliness and social/physical disconnection (Cabedo-Mas et al, 2020;MacDonald et al, 2020;Vandenberg et al, 2021).…”
Section: Caregivers' and Children's Musical Behaviors During Social Dmentioning
confidence: 99%